2001
DOI: 10.1086/322979
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Intermediate‐Mass Elements in Classical Novae: From Si to Ca

Abstract: Thermonuclear runaways driven by accretion into degenerate white dwarf cores are the source that power classical nova outbursts. In this paper, we identify the dominant nuclear paths involved in the synthesis of intermediate-mass elements, from Si to Ca, during such violent events. New evolutionary sequences of 1.35 M ⊙ ONe novae have been computed, using updated nuclear reaction rates. The main nuclear activity in this region is powered by the leakage from the NeNa-MgAl region, where the activity is confined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 40 publications
7
142
3
Order By: Relevance
“…By developing a radioactive 18 Ne beam through the 3 He( 16 O, 18 Ne)n reaction, the 18 Ne(α,p) 21 Na process could be studied at astrophysical energies to provide a link between the Hot CNO cycle and the rp-process [14]. Another measurement relevant to astrophysics can be performed at EXOTIC such as the 30 P(p,γ) 31 S with a 30 P beam, essential for the production of heavy elements (from Si to Ca) in the explosion of ONe novae and in particular to explain the anomalously high 30 Si/ 28 Si rate measured in pre-solar grains of possible ONe novae origin [16]. Moreover, experiments based on the Trojan Horse Method (THM) [17] are considered.…”
Section: Experimental Program and Perspectivesmentioning
confidence: 99%
“…By developing a radioactive 18 Ne beam through the 3 He( 16 O, 18 Ne)n reaction, the 18 Ne(α,p) 21 Na process could be studied at astrophysical energies to provide a link between the Hot CNO cycle and the rp-process [14]. Another measurement relevant to astrophysics can be performed at EXOTIC such as the 30 P(p,γ) 31 S with a 30 P beam, essential for the production of heavy elements (from Si to Ca) in the explosion of ONe novae and in particular to explain the anomalously high 30 Si/ 28 Si rate measured in pre-solar grains of possible ONe novae origin [16]. Moreover, experiments based on the Trojan Horse Method (THM) [17] are considered.…”
Section: Experimental Program and Perspectivesmentioning
confidence: 99%
“…In this paper we compare the information extracted from such grains with the theoretical yields obtained from recent numerical calculations of nova outbursts (José & Hernanz 1998;Hernanz et al 1999;José et al 1999José et al , 2001 and unpublished data). These calculations were carried out with the one-dimensional, implicit, lagrangian, hydrodynamic code SHIVA (see José & Hernanz 1998 for details) that follows the course of the explosion from the onset of accretion up to the expansion and ejection stages.…”
Section: Introductionmentioning
confidence: 95%
“…1). Explosions involving ONe white dwarfs yield low Figure 1 Nitrogen versus carbon isotopic ratios, obtained from a series of hydrodynamic models for both CO and ONe novae (José & Hernanz 1998;Hernanz et al 1999;José et al 1999José et al , 2001and unpublished data). Data from presolar nova grains isolated from the Acfer 094 and Murchison meteorites (Amari et al 2001;Amari 2002) are also shown.…”
Section: Nitrogen and Carbon Isotopic Ratiosmentioning
confidence: 99%
“…The first case concerns the 30 P(p,γ) 31 S reaction rate which influences the abundances of heavy elements up to Ca isotopes from ONe novae ejecta [1] and also influences the 28/30 Si abundance ratio used to characterize pre-solar grains as being of novae origin [2].The second case relates to the cosmic gamma-ray emitter 26 Al,which observations have shown predominantly originates from regions of massive star formation [3].…”
Section: Introductionmentioning
confidence: 99%